An Empirical Study on the Prevalence and Multidrug Resistance Profiles of Salmonella and Campylobacter Species: A One Health Context - Muhammad Talha Aziz; Sadaf Sultana; Rabiya Sultana; Muhammad Saad Yousaf; Syed Muhammad Sibtain Shah; Madiha Hassan; Ayesha Tariq; Ieman Tariq; Shafiq Ur Rehman (Open Access Public Health and Health Administration Review, 2026)
Salmonella and Campylobacter are foodborne pathogens that pose public health risks, particularly in commercial poultry production, where antimicrobial resistance may compromise the treatment of infected birds and undermine food safety. The present cross-sectional study aimed to determine the prevalence, antimicrobial resistance profile, and multidrug resistance (MDR) pattern of Salmonella and Campylobacter in commercial broiler farms of Punjab, Pakistan. Samples (ecal contents, cloacal swabs, bootsocks, and fecal grabs) were taken from 70 farms, with a total of 350 samples collected and processed by microbiological and molecular techniques. The overall Salmonella prevalence was 22.0% (77 samples were positive), and the overall Campylobacter prevalence was 34.0% (119 samples were positive). Campylobacter prevalence was also found to be highest in bootsocks (48.6%), whereas the prevalence of Salmonella was highest in bootsocks (31.4%). The highest prevalence of both pathogens was found on small farms. The highest resistance level was seen for Salmonella isolates against tetracycline (80.5%) and nalidixic acid (71.4%), and 61.0% were considered MDR. The antimicrobial resistance rate for Campylobacter was high for tetracycline (89.1%), ciprofloxacin (81.5%), and nalidixic acid (76.5%), and the MDR rate was 93.3%. Pathogen prevalence was significantly associated with farm size, antimicrobial use, and biosecurity. These findings indicate a threat from One Health and underscore the importance of better biosecurity, responsible use of antimicrobials, surveillance, and targeted interventions for commercial broiler production.